2020
DOI: 10.4239/wjd.v11.i12.622
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-dependent activation of glucose transport in adipocytes by catecholamines is not mediatedviaadrenoceptor stimulation or monoamine oxidase activity

Abstract: BACKGROUND Benzylamine and methylamine activate glucose uptake in adipocytes. For tyramine, this effect has even been extended to cardiomyocytes. AIM To investigate the effects of catecholamines and other amines on glucose uptake. METHODS A screening compared 25 biogenic amines on 2-deoxyglucose (2-DG) uptake activation in rat adipocytes. Pharmacological approaches and transgenic mouse models were then used to decipher the mode of action of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…It was immediately digested by collagenase in Krebs-Ringer buffer containing 15 mmol/L bicarbonate, 10 mmol/L HEPES, 2 mmol/L pyruvate, and 3.5% bovine serum albumin. Separation, washing, and dilution of the buoyant adipocytes were performed in the immediate continuity at 37 °C with fresh buffer prior to the functional assays, which were performed as previously described[ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was immediately digested by collagenase in Krebs-Ringer buffer containing 15 mmol/L bicarbonate, 10 mmol/L HEPES, 2 mmol/L pyruvate, and 3.5% bovine serum albumin. Separation, washing, and dilution of the buoyant adipocytes were performed in the immediate continuity at 37 °C with fresh buffer prior to the functional assays, which were performed as previously described[ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The radiolabeled non-metabolizable analog of glucose, 3 H-2-DG, was used at 0.1 mmol/L for hexose uptake assays as described previously[ 20 ], save that the assays lasted 5 min instead of 10 min for human fat cells, which are less metabolically active.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report, we demonstrated that catecholamines such as noradrenaline and adrenaline (also named norepinephrine and epinephrine) are capable of activating glucose transport in rodent adipocytes, essentially in the presence of vanadium[ 1 ]. These observations, providing the basis for novel research of vanadium/amine complexes exhibiting antidiabetic properties of the metal ions with less toxicological issues, needed further verification.…”
Section: Introductionmentioning
confidence: 99%